Entrepreneurship dalam Pendidikan Pesantren: Entrepreneurship in Islamic Boarding School Education - Nur Khikmah; Moh. Sugeng Sholehuddin; Abdul Khobir; Sopiah Sopiah (ITScience (Information Technology and Science), 2026)
Entrepreneurship education in Islamic boarding schools (pesantren) is a strategic step in facing the challenges of globalisation and the dynamics of the modern economy. Traditionally known as religious-based educational institutions, Islamic boarding schools have great potential to become centres of community economic empowerment. This study aims to examine the concept of entrepreneurship education in Islamic boarding schools and its role in building community independence by integrating Islamic values and practical skills relevant to everyday life. The method used is qualitative research with a library research approach, which analyses scientific literature on the concept and implementation of entrepreneurship in Islamic boarding school education. The results show that entrepreneurship education in Islamic boarding schools is not only oriented towards mastering theory but also emphasises hands-on practice through business units, skills training, and experiential learning. The integration of Islamic values, such as honesty, responsibility, and justice, is the main foundation for shaping the ethical character of Muslim entrepreneurs. In addition, the roles of kyai (Islamic clerics) and ustadz (Islamic religious teachers) as mentors, along with the support of the Islamic boarding school environment, are important factors in the successful implementation of entrepreneurship education. Thus, Islamic boarding schools serve not only as centres of religious education but also as agents of social and economic change, capable of producing independent, creative, and highly competitive generations. Entrepreneurship education in Islamic boarding schools is expected to help reduce unemployment and sustainably improve community welfare